Light perception and signalling by phytochrome A - Casal, J J (Journal of experimental botany, 2014)
© The Author 2013. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.